Effect of water-based drilling mud on benthic organisms. - H., C. Lai
The effect of water-based drilling mud (WBM) was studied with respect to its acute toxicity on the prawn tiger, Penaeus monodon, and recolonisation by benthos on sediment incorporated with several concentrations of drilling mud.